Upaya Kepolisian Dalam Penanggulangan Kenakalan Remaja di Surakarta - Widayanto, Yusuf, Dr. Natangsa Surbakti, SH, M.Hum, Marisa Kurnianingsih, SH. M.Kn. MH (2016)
Adolescence is a stage of life that is transitional and unstable. Juvenile delinquency is an aberrant behavior or unlawful. Types are also varied, such as drug abuse, criminal acts, to sexual harassment. It can be triggered by a variety of demands and stress. For example, finding a job in a competitive environment, develop relationships with others, demands for self-organization, and adaptation to technology. In addition, many teenagers experiencing anxiety and stress related to personal safety and security. Juvenile delinquency cause material loss and inner misery both to the actors themselves as well as for victims. For the various juvenile delinquency prevention efforts both penal and non-penal made by various parties, including the police. Abatement is penal in the form it processes juvenile offenders legally. In non penal overcome by the police in the form of counseling, patrol, coaching, as well as raids. This study uses descriptive non-doctrinal. Using this type of primary and secondary data. Data collection techniques used through interviews and literature study. By using qualitative data analysis. Based on the results of research and discussion, it can be concluded that the efforts of the police in the prevention of juvenile delinquency in the form of preventive and repressive. Abatement preventive care such as certain places, patrol, counseling, conveying messages of social order, traffic management, safety riding training. Abatement repressive form of diversion, manufacture affidavit, coaching, penilangan, rehabilitation. Barriers that prevent the police in tackling juvenile delinquency is difficult to reach an agreement in an effort kinship, verdict too light, insufficient rule of law, ignorance of the law being in force, counseling schedule incompatibility with the agenda in schools, lack of legal awareness in berlalu- traffic, lack of coordination with the Dispora and the public.